Cultivating Student Voice and Choice in Open and Networked Learning Environments - Paskevicius, Michael; Harrison, Michelle; Childs, Elizabeth (Proceedings of the International Conference on Networked Learning, 2026)
Networked learning environments are evolving rapidly beyond the confines of centralised learning and content management systems. Our shared approach to designing networked learning is grounded in a student owned and federated model that allows for student agency and ownership of a portfolio of their learning that can be personalized and curated by the learner. In these open and networked learning environments, there is an opportunity for the creation of multiple artefacts and possibilities for remixing, reusing, and creating new and novel experiences for other students and educators to interact with. This requires students to consider and reflect on what they decide to create and how it is shared more broadly while also attending to ethical concerns. This design-based research study investigated the student experience and perceptions of using a networked learning environment to support the creation of community-generated, non-hierarchical teaching and learning resource(s) using a multiple perspectives reflection framework. The tool and framework were used in two graduate level courses offered over a two-year period involving seven participants. Eleven posts and their associated comments/discussions/artifacts were analysed as part of this project. This research reports on the preliminary findings from the evaluation and reflection phase of this three-phased research project. Initial analysis showcases the importance of interactivity, agency, accessibility, structure, and voice in the co-creation of meaningful, engaging, critical learning experiences. These findings provide useful input for the next phase of this tool and for further understanding of what students experience when working in open and networked learning environments.